2022
DOI: 10.2147/ppa.s353525
|View full text |Cite
|
Sign up to set email alerts
|

The Health-Related Quality of Life of Patients with Type 2 Diabetes in Saudi Arabia

Abstract: Objective Diabetes mellitus (DM) is one of the most common chronic diseases in the world. Diabetes mellitus has a major effect on patients’ quality of life, especially when the patient has other comorbidities. Therefore, this study aims to assess the quality of life of type 2 diabetic patients in the Al-Ahsa region of Saudi Arabia. Methods This was a cross-sectional study, which was conducted from September 2020 to May 2021 on patients with type 2 diabetes mellitus in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
1
5
2
1
Order By: Relevance
“…However, a study done in Saudi Arabia that used the EQ-5D instrument found different results than our study ( 23 ), with a higher percentage of Saudi Arabia patients reporting problems in all sub-scales than the Kuwaiti patients in our study. The Saudi Arabia study participants reported more problems in mobility, self-care, usual activities, pain and discomfort, and depression and anxiety, than our study's participants.…”
Section: Discussioncontrasting
confidence: 99%
“…However, a study done in Saudi Arabia that used the EQ-5D instrument found different results than our study ( 23 ), with a higher percentage of Saudi Arabia patients reporting problems in all sub-scales than the Kuwaiti patients in our study. The Saudi Arabia study participants reported more problems in mobility, self-care, usual activities, pain and discomfort, and depression and anxiety, than our study's participants.…”
Section: Discussioncontrasting
confidence: 99%
“…Higher monthly income earners in this study demonstrated a lower risk of mobility issues, pain or discomfort, and difficulties performing usual activities, self-care and anxiety. Higher monthly income generally led to an improved HRQoL, which is consistent with research findings from other studies [ 37 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…Chẳng hạn tại Thụy Điển về vai trò của số năm mắc đái tháo đường với việc dự báo chất lượng cuộc sống, nghiên cứu trước đây cho rằng mắc bệnh càng trẻ thì chất lượng cuộc sống càng giảm [7]. Nghiên cứu tại Saudi Arabia cho thấy tuân thủ điều trị sẽ có chất lượng cuộc sống tốt hơn nhóm không tuân thủ [10], kết quả nghiên cứu của tôi không cùng xu hướng với nghiên cứu này. Sự khác biệt có lẽ do đặc điểm của đối tượng nghiên cứu, chúng tôi tập trung vào nhóm có biến chứng tim mạch, trong khi các nghiên cứu khác tập trung vào nhóm đái tháo đường nói chung.…”
Section: Bàn Luậnunclassified